2019
DOI: 10.1073/pnas.1900161116
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanics of cellulose deformation reveal molecular defects that facilitate natural deconstruction

Abstract: Technologies surrounding utilization of cellulosic materials have been integral to human society for millennia. In many materials, controlled introduction of defects provides a means to tailor properties, introduce reactivity, and modulate functionality for various applications. The importance of defects in defining the behavior of cellulose is becoming increasingly recognized. However, fully exploiting defects in cellulose to benefit biobased materials and conversion applications will require an improved unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 49 publications
5
65
0
Order By: Relevance
“…Moreover, computational modeling based on transmission electron microscopy revealed that cellulose microfibrils kink along their lengths in their energy minimized state [40]. Ciesielski et al proposed that highly crystalline cellulose fibrils kink to release internal stresses [41]; we speculate that we observed this stress release due to the cellulose fibrils being actively hydrolyzed. Although the process of kinking was only observed twice, kinked fibrils were frequently observed in the experimental samples.…”
Section: Additional Evidence For Cel7a Activity In the Single-moleculmentioning
confidence: 61%
“…Moreover, computational modeling based on transmission electron microscopy revealed that cellulose microfibrils kink along their lengths in their energy minimized state [40]. Ciesielski et al proposed that highly crystalline cellulose fibrils kink to release internal stresses [41]; we speculate that we observed this stress release due to the cellulose fibrils being actively hydrolyzed. Although the process of kinking was only observed twice, kinked fibrils were frequently observed in the experimental samples.…”
Section: Additional Evidence For Cel7a Activity In the Single-moleculmentioning
confidence: 61%
“…The xyloglucan backbone is synthesized by cellulose synthase‐like C (CslC) family members; the Arabidopsis cslc4 mutant and the quintuple mutant cslc4 cslc5 cslc6 cslc8 cslc12 have undetectable xyloglucan levels (Cocuron et al, 2007; Kim et al, 2020). The enzymatic activity of AtCslC4 has been examined (Cocuron et al, 2007).…”
Section: Cell Wall Composition and Biosynthesismentioning
confidence: 99%
“…Cellulose has been the subject of many molecular simulation studies. Some of these studies focus only at the surface phenomena and modifications of CNC, (Chen et al 2017;Zhou et al 2015;Bergenstråhle et al 2008;Paajanen et al 2016;Chundawat et al 2011) while many others simulate whole CNC, both at atomistic (Chen et al 2017;Zhou et al 2015;Bergenstråhle et al 2008;Paajanen et al 2016;Chundawat et al 2011;Matthews et al 2006;Conley et al 2016;Oehme et al 2015;Djahedi et al 2015;Paajanen et al 2019;Ciesielski et al 2019) and coarsegrained representations (López et al 2009;Wohlert and Berglund 2011;López et al 2015;Mehandzhiyski and Zozoulenko 2019;Glass et al 2012;Fan and Maranas 2015;Markutsya et al 2013;Shishehbor et al 2018;Shishehbor and Zavattieri 2019;Ramezani and Golchinfar 2019;Srinivas et al 2011;Poma et al 2015Poma et al , 2016Poma et al , 2017. All-atom molecular dynamics (AA-MD) studies are able to simulate the crystal structure of cellulose in a perfect agreement with the experimental crystal structure of different cellulose allomorphs and provide a detailed atomistic picture for the structure and dynamics of CNC (Chundawat et al 2011).…”
Section: Introductionmentioning
confidence: 99%